1998
DOI: 10.1111/j.1600-0668.1998.t01-2-00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temperature and Humidity on the Perception of Indoor Air Quality

Abstract: Sensory responses to clean air and air polluted by five building materials under different combinations of temperature and humidity in the ranges 18‐28°C and 30‐70%RH were studied in the laboratory. A specially designed test system was built and a set of experiments was designed to observe separately the impact of temperature and humidity on the perception of air quality/odour intensity, and on the emission of pollutants from the materials. This paper reports on the impact on perception. The odour intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
236
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(283 citation statements)
references
References 10 publications
27
236
1
2
Order By: Relevance
“…The study demonstrated that during continuous exposures lasting more than 4 hours, temperature ramps contributed to enhanced intensity of headaches and other general SBS symptoms. This is in agreement with results of previous studies showing that increasing indoor temperatures in buildings may be associated with increased intensity of symptoms of fatigue, headache and difficulty in thinking clearly [6]. Also, a field study by Mendell et al [7] found significant effects of temperature on the prevalence of SBS symptoms, even within the temperature comfort zone.…”
Section: Introductionsupporting
confidence: 82%
“…The study demonstrated that during continuous exposures lasting more than 4 hours, temperature ramps contributed to enhanced intensity of headaches and other general SBS symptoms. This is in agreement with results of previous studies showing that increasing indoor temperatures in buildings may be associated with increased intensity of symptoms of fatigue, headache and difficulty in thinking clearly [6]. Also, a field study by Mendell et al [7] found significant effects of temperature on the prevalence of SBS symptoms, even within the temperature comfort zone.…”
Section: Introductionsupporting
confidence: 82%
“…Many practitioners report that the stillness of air within the occupied zone of most air-conditioned spaces (as mandated by current standards like ASHRAE Standard 55) is associated with complaints of poor quality ''dead'' air. Perhaps elevated air speeds within the occupied zone cannot only permit thermal comfort to be achieved at higher temperatures (thereby saving on refrigeration energy), but also improve perceived air quality, or at least offset the enthalpy effect referred to in [25]. The work of Toftum et al [19], discussed earlier with regard to the role of personal control, would certainly lend support to this idea.…”
Section: Beyond Thermal Comfortmentioning
confidence: 60%
“…Research findings often suggest conflicting goals for the indoor environment. For example, recent work has shown that perceptions of indoor air quality are improved when temperatures are cooler, and engineers can therefore, decrease ventilation rates [25] by decreasing indoor temperatures. But what are the energy implications of this finding?…”
Section: Beyond Thermal Comfortmentioning
confidence: 99%
“…Inter-category relationships (interaction effect [53]) are not considered in the IEQ model framework. None of the models presented here discuss the interaction between IEQ categories, for example, higher thermal comfort is often associated with higher indoor air quality [54].…”
Section: Discussionmentioning
confidence: 99%